2015
DOI: 10.1109/tamd.2015.2440298
|View full text |Cite
|
Sign up to set email alerts
|

Discriminating Bipolar Disorder From Major Depression Based on SVM-FoBa: Efficient Feature Selection With Multimodal Brain Imaging Data

Abstract: Discriminating between bipolar disorder (BD) and major depressive disorder (MDD) is a major clinical challenge due to the absence of known biomarkers; hence a better understanding of their pathophysiology and brain alterations is urgently needed. Given the complexity, feature selection is especially important in neuroimaging applications, however, feature dimension and model understanding present serious challenges. In this study, a novel feature selection approach based on linear support vector machine with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
4

Relationship

4
6

Authors

Journals

citations
Cited by 90 publications
(53 citation statements)
references
References 52 publications
4
49
0
Order By: Relevance
“…We observed that, compared to the MDD group, the FNC of the BD group exhibited higher FC strengths and also was characterized by more efficient topological structures based on measures obtained using graph theory at the functional-network-level in prefrontal cortex as well as at the whole-brain-level. In particular, our findings revealed that the FC strengths and corresponding graph structures which differentiate BD and MDD were mainly located in prefrontal networks including the DLPFC and VLPFC as well as ACC, which is consistent with findings in (Jie et al, 2015). Greater depressive symptom severity correlated with less interconnected structure in prefrontal cortical areas in the patients from both the BD and MDD groups.…”
Section: Discussionsupporting
confidence: 91%
“…We observed that, compared to the MDD group, the FNC of the BD group exhibited higher FC strengths and also was characterized by more efficient topological structures based on measures obtained using graph theory at the functional-network-level in prefrontal cortex as well as at the whole-brain-level. In particular, our findings revealed that the FC strengths and corresponding graph structures which differentiate BD and MDD were mainly located in prefrontal networks including the DLPFC and VLPFC as well as ACC, which is consistent with findings in (Jie et al, 2015). Greater depressive symptom severity correlated with less interconnected structure in prefrontal cortical areas in the patients from both the BD and MDD groups.…”
Section: Discussionsupporting
confidence: 91%
“…It enables robust identification of correspondence among N diverse data types and enables one to investigate the important question of whether certain disease risk factors are shared or are distinct across multiple modalities, which can also serve as multimodal feature selection method for schizophrenia (Sui et al, 2013a, 2013b). Similarly, Jie et al adopted SVM-FoBa to classify between bipolar versus unipolar disorders by combining GM and ALFF features, achieving an accuracy of 92% This suggests that using complimentary multimodal biomarkers may be more informative and effective to discriminate brain disorders (Jie et al, 2015). …”
Section: Machine Learning In Neuroimaging: Shortcomings and Emergimentioning
confidence: 99%
“…Additionally, nonimaging measures have also been used in depression . Thus, it is important to study how multimodal MRI in conjunction with nonimaging features affects prediction models of depression . Each MRI modality represents different view of the brain, and data fusion capitalizes on the strengths of each modality and their inter‐relationships in a joint analysis to unravel the pathophysiology of brain disease .…”
Section: Future Directionsmentioning
confidence: 99%